Conserved regions from Plasmodium falciparum MSP11 specifically interact with host cells and have a potential role during merozoite invasion of red blood cells (2010)
Despite significant global efforts, a completely effective vaccine against Plasmodium falciparum, the species responsible for the most serious form of malaria, has not been yet obtained. One of the most promising approaches consists in combining chemically synthesized minimal subunits of parasite proteins involved in host cell invasion, which has led to the identification of peptides with high binding activity (named HABPs) to hepatocyte and red blood cell (RBC) surface receptors in a large number of sporozoite and merozoite proteins, respectively. Among these proteins is the merozoite surface protein 11 (MSP11), which shares important structural and immunological features with the antimalarial vaccine candidates MSP1, MSP3, and MSP6. In this study, 20-mer-long synthetic peptides spanning the complete sequence of MSP11 were assessed for their ability to bind specifically to RBCs. Two HABPs with high ability to inhibit invasion of RBCs in vitro were identified (namely HABPs 33595 and 33606). HABP-RBC bindings were characterized by means of saturation assays and Hill analysis, finding cooperative interactions of high affinity for both HABPs (nH of 1.5 and 1.2, Kd of 800 and 600nM for HABPs 33595 and 33606, respectively). The nature of the possible RBC receptors for MSP11 HABPs was studied in binding assays to enzyme-treated RBCs and cross-linking assays, finding that both HABPs use mainly a sialic acid-dependent receptor. An analysis of the immunological, structural and polymorphic characteristics of MSP11 HABPs supports including these peptides in further studies with the aim of designing a fully effective protection-inducing vaccine against malaria. © 2010 Wiley-Liss, Inc.